Novel micro-channel cooler for high-power diode laser arrays - Kozłowska, Anna; Teodorczyk, Marian; Dąbrowska-Tumańska, Elżbieta; Chmielewski, Marcin; Podniesiński, Dariusz; Maląg, Andrzej (Photonics Letters of Poland, 2014)
The construction of novel micro-channel cooler that allows for high packaging density of laser diode arrays is presented. Its main element is the micro-channel copper plate with micro-pipes that transport cooling liquid in the vicinity of diode laser array. The prototype series of the coolers was manufactured and tested. The experimental arrangements for investigations of thermal properties and micro-photoluminescence measurements of the devices were built. Experimental results indicate that the proposed cooler is interesting solution for high-power diode laser arrays. Full Text: PDF References V.K. Krause et al., "Microchannel coolers for high-power laser diodes in copper technology", Proc. SPIE 2148, 351 (1994). CrossRef Y. Karni, G. Klumel, M. Levy, Y. Berk, Y. Openhaim, Y. Gridish et al., "Active cooling solutions for high power laser diodes stacks", Proc. SPIE 6876, 687604-1 (2008). CrossRef J. Vetrovec, "Improved cooling for high-power laser diodes", Proc. SPIE 6876, 687603-1 (2008). CrossRef R. Feeler, "Next-generation microchannel coolers", Proc SPIE 6876, 687608-1-8 (2008). CrossRef J. Dix, A. Jokar, R. Martinsen, "Enhanced microchannel cooling for high-power semiconductor diode lasers", Proc. SPIE 6876, 687606-1-10 (2008). CrossRef J. Wang et al., "High-power semiconductor laser array packaged on microchannel cooler using gold-tin soldering technology", Proc. SPIE 8241, 82410H-1-9 (2012). CrossRef Z. Liu, G. Fang, K. Feng, "High packing density laser diode stack arrays using Al-free active region laser bars with a broad waveguide and discrete copper microchannel-cooled heatsinks", Chin. Opt. Lett. 7, 214 (2009). CrossRef J.W. Tomm, J. Jimenez, Eds, Quantum-well laser array packaging (New York, McGraw-Hill 2007). M. Leers, K. Boucke, Proc. IEEE Electr. Comp. Techn. Conf. 1011 (2008). A. Maląg, A. Jasik, M. Teodorczyk, A. Jagoda, A. Kozłowska, "High-Power Low Vertical Beam Divergence 800-nm-Band Double-Barrier-SCH GaAsP–(AlGa)As Laser Diodes", IEEE Photon. Tech. Lett. 18, 1582 (2006). CrossRef